IL23R and IL12B SNPs and Haplotypes Strongly Associate with Crohn's Disease Risk in a New Zealand Population. (21st November 2010) - Ferguson, Lynnette R.; Han, Dug Yeo; Fraser, Alan G.; Huebner, Claudia; Lam, Wen Jiun; Morgan, Angharad R.
Abstract : DNA samples from 339 Crohn's disease (CD) and 407 randomly selected controls from the Auckland (New Zealand) IBD project, were genotyped for five common single nucleotide polymorphisms in IL-23R (rs11805303, rs7517847, rs1343151, rs11209026, and rs10889677) and two in IL-12B (rs1363670 and rs6887695). While the IL-12B variants did not show an overall association and other IL23R variants led to minor changes in the risk of CD, rs1343151 and/or rs7517847 variants in the IL-23R gene strongly reduced the risk of developing CD at both allelic and genotype levels. A significantly decreased risk of first diagnosis of childhood CD was observed in individuals carrying the A allele of rs1343151, or between 17–40 y in individuals carrying the G allele in rs7517847 of IL-23R . A significantly decreased risk of ileocolonic or structuring disease was observed in individuals carrying the A allele in either rs11209026 or rs1343151, or the G allele in rs7517847 of IL-23R, and when such individuals did develop the disease, they were unlikely to require a bowel resection. Certain haplotypes very strongly modified risk. There was evidence for interactions of IL-23R variants with the NOD2 wild-type (d/d) genotype. Down-regulating the function of the IL-23R gene may decrease CD risk in the normal population.